West2East: exploiting WEb Service Technologies to Engineer Agent-based SofTware. (14th December 2007) - Casella, Giovanni; Mascardi, Viviana
This paper describes West2East, a computer-aided Agent-Oriented Software Engineering (AOSE) toolkit aimed at supporting the implementation of Multiagent Systems (MASs). West2East exploits languages for Web Services (WSs) for sharing Agent Interaction Protocols (AIPs), modelled using AUML, across the web, and Computational Logic to reason about them. In particular, West2East offers libraries for the translation of AIPs represented in AUML into 1) a textual notation proposed by Winikoff; 2) an XML notation proposed by ourselves; 3) a couple of WS-BPEL and WSDL documents; and 4) a Prolog term. It also offers 5) a mechanism for allowing agents that read a published AIP to reason about it before engaging in a dialogue with its publisher, and 6) libraries for the automatic generation of an executable program compliant with the original interaction protocol.